2022
DOI: 10.1128/spectrum.00518-22
|View full text |Cite|
|
Sign up to set email alerts
|

FXR Signaling-Mediated Bile Acid Metabolism Is Critical for Alleviation of Cholesterol Gallstones by Lactobacillus Strains

Abstract: Cholesterol gallstone (CGS) disease is prevalent worldwide. None of the medical options for prevention and treatment of CGS disease are recommended, and surgical management has a high rate of recurrence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 69 publications
0
13
0
Order By: Relevance
“…Previous studies have demonstrated that Lactobacillales can effectively suppress the expression of farnesoid X receptor (FXR) antagonists, such as tauro-α-muricholic acid and tauro-β-muricholic acid. 42 This suppression leads to an increase in FXR activity, resulting in reduced bile acid and cholesterol production in the liver and circulation. Moreover, alterations in gut microbiology have been found to contribute to pancreatic diseases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have demonstrated that Lactobacillales can effectively suppress the expression of farnesoid X receptor (FXR) antagonists, such as tauro-α-muricholic acid and tauro-β-muricholic acid. 42 This suppression leads to an increase in FXR activity, resulting in reduced bile acid and cholesterol production in the liver and circulation. Moreover, alterations in gut microbiology have been found to contribute to pancreatic diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, we identified the risk factor posed by the genus‐level Peptococcus , which is consistent with previous research in this area. Previous studies have demonstrated that Lactobacillales can effectively suppress the expression of farnesoid X receptor (FXR) antagonists, such as tauro‐α‐muricholic acid and tauro‐β‐muricholic acid 42 . This suppression leads to an increase in FXR activity, resulting in reduced bile acid and cholesterol production in the liver and circulation.…”
Section: Discussionmentioning
confidence: 99%
“…It governs the synthesis of BAs mainly by downregulating the expression of cholesterol 7α-hydroxylase via both the intrahepatic FXR-small heterodimer partner and the extrahepatic FXR-fibroblast growth factor 19 (FGF19)fibroblast growth factor receptor pathways. 21 FXR activation promotes BAs secretion by upregulating the bile salt export pump and multiple related proteins (e.g., multidrug resistance-associated protein 2/3 and ATPbinding cassette subfamily G member 5/8) [22][23][24] and inhibits their reabsorption by downregulating sodiumdependent bile acid transporter 25 and sodium/taurocholate cotransporting polypeptide. 26 In addition, this NR plays an essential role in the metabolism of lipids and glucose.…”
Section: Beneficial Effects Of Fxr Activationmentioning
confidence: 99%
“…Intervention of lithogenic-diet (LD)-fed mice with Lactobacillus reuteri and Lactobacillus plantarum regulated the gut microbiota, which increased the relative abundance of Muribaculaceae and Akkermansia in the former and latter, respectively. These strains may alleviate gallstones and hepatic steatosis by activating FXR and inhibiting the activities of hepatic sterol 7α-hydroxylase (CYP7A1) and hepatic sterol 7α-hydroxylase (CYP7B1) ( 114 ). The probiotic Prevotella copri can significantly increase the intestinal microbiota diversity and activate the FXR-Cyp7a1 signaling pathway to inhibit BA synthesis to improve the progression of cholestasis and liver fibrosis in PSC mouse models ( 115 ).…”
Section: Biotherapiesmentioning
confidence: 99%